New prostate cancer grade grouping system predicts survival after radical prostatectomy - Andrew Erickson; Kevin Sandeman; Kanerva Lahdensuo; Stig Nordling; Markku Kallajoki; Heikki Seikkula; Anna Bützow; Hanna Vasarainen; Peter J. Boström; Pekka Taimen; Antti Rannikko; Tuomas Mirtti (W.B. Saunders, 2022)
Histological Gleason grading of prostate cancer has been through modifications and conjoined into a Grade Grouping system recently. The aim of this study was to determine whether the new Grade Grouping system predicts disease-specific and all-cause mortality after radical prostatectomy. We constructed a clinical database consisting of all consecutively radical prostatectomy–treated men between 1983 and 1998 and between 2000 and 2005 at the Helsinki University Hospital and at the Turku University Hospital, respectively. Patients' all-cause and prostate cancer–specific mortality information was updated in November 2015 from the Finnish Cancer Registry. Secondary therapy information was also available from the patients' records at Helsinki. Univariate and multivariate statistical analyses were performed to assess predictive significance of the Grade Grouping system. Grade Grouping associated independently with increased risk of prostate cancer–specific mortality within 15 years of follow-up in a multivariable model containing age at operation, diagnostic prostate-specific antigen, pathological stage and lymph node status at operation. Additionally, the all-cause mortality-free survival time and time to secondary therapies were different between the Grade Groups, emphasized in the subanalysis of Grade Groups 1-2 versus Grade Groups 3-5. We can conclude that the new Grade Grouping system is feasible in predicting prostate cancer–specific survival after radical surgical treatment. Grade Grouping offers a simpler way to interpret the predicted course of the disease to individual patients and thus may help in justifying more conservative follow-up approaches, especially in the lower Grade Group patients.